Wartość pracy dla pracujących osób pozbawionych wolności - Lenart-Kłoś, Katarzyna (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The aim of this paper is to present the value of labour in the opinion of working prisoners. Work as a value has been presented and its understanding in the holistic way as a multidimensional process has been underlined. Nowadays labour is perceived as one of the most important instruments of resocialization. It enables reducing prisonization in total institutions. The results of the research show that the working prisoners treat labour as a privilege rather than a duty. They would not like to leave their job, no matter whether they have applied for it on their own or it has been commissioned to them and whether they receive a salary.